Circadian variation of heart rate is affected by environment: a study of continuous electrocardiographic monitoring in members of a symphony orchestra. Issue 6 (December 1990) - Mulcahy, D; Keegan, J; Fingret, A; Wright, C; Park, A; Sparrow, J; Curcher, D; Fox, K M
Abstract : Twenty four hour ambulatory ST segment monitoring was performed on 48 members (43 players and five members of the management/technical team) of the British Broadcasting Corporation (BBC) symphony orchestra without a history of cardiac disease. This period included final rehearsals and live performances (for audience and radio) of music by Richard Strauss and Mozart at the Royal Festival Hall (n = 36) and Rachmaninov and Tchaikovsky at the Barbican Arts Centre (n = 21). During the period of monitoring one person (2%) had transient ST segment changes. Mean heart rates were significantly higher during the live performances than during the rehearsals. Mean heart rates during the live performance of Rachmaninov and Tchaikovsky were significantly higher than during Strauss and Mozart in those (n = 6) who were monitored on both occasions. Mean heart rates in the management and technical team were higher than those of the players. The recognised circadian pattern of heart rate, with a peak in the morning waking hours, was altered similarly during both concert days, with a primary peak occurring in the evening hours and a lesser peak in the morning for both musicians and management/technical staff. This study showed that environmental factors are of primary importance in defining the circadian pattern of heart rate. This has important implications when identifying peak periods of cardiovascular stress and tailoring drug treatment for patients with angina pectoris.